At-home use of parasacral transcutaneous electrical nerve stimulation for pediatric voiding dysfunction: a randomized controlled trial to assess its safety and feasibility - Malhotra, Neha R.; Siegal, Alexandra R.; Lange, Suzanne M.; Cervantez, DeeAnn; White, Heidi K.; Hannon, AnnMarie; Schaeffer, Anthony J.; Lau, Glen A. (Frontiers in Pediatrics, 2023)
Introduction Treating pediatric voiding dysfunction involves behavioral changes that require significant time or medications that are often avoided or discontinued due to side effects. Using parasacral transcutaneous electrical nerve stimulation (PTENS) has shown to have reasonable efficacy, but the safety and feasibility of its off-label use for pediatric voiding dysfunction are not well-established. Concerns have also been raised over treatment adherence. In-home therapy might improve adherence compared with office-based therapy; however, no studies have evaluated in-home feasibility to date. This study aims to assess the safety and feasibility of off-label use of PTENS for pediatric voiding dysfunction. Materials and methods A single-institution prospective, randomized controlled study was conducted from March 2019 to March 2020. Participants aged 6–18 years diagnosed with voiding dysfunction, overactive bladder, or urinary incontinence were eligible for the study. Those with known neurologic disorders, implanted electrical devices, anatomic lower urinary tract abnormality, and recurrent urinary tract infections and those taking bladder medications were excluded. Children with primary monosymptomatic nocturnal enuresis were also excluded due to previous work suggesting a lack of efficacy. Participants were randomly assigned to receive 12 weeks of urotherapy alone (control) or urotherapy plus at-home PTENS treatment. Families were contacted weekly to assess for adverse events (AEs) and treatment adherence. The primary and secondary outcomes were safety, defined as the absence of AEs and treatment adherence, respectively. Results A total of 30 eligible participants were divided into two groups, with 15 participants in each arm. The median age was 9.4 years (interquartile range: 7.7–10.6). In total, 60% were male. Baseline demographics and urotherapy compliance were similar between the two groups. With PTENS use, two AEs were reported, including mild pruritus at the pad site and discomfort when removing pads, while no AEs were noted in the control group. In total, 60% of patients completed three 30-min sessions per week, and all participants were able to complete treatment sessions for at least 10 weeks, involving 30 min of PTENS treatment each time. Conclusion This randomized controlled study confirms that at-home use of PTENS is feasible with reasonable treatment adherence and minimal AEs. Future collaborative, multi-institutional studies may better determine the efficacy of this treatment modality.